Homeowners' financial vulnerability over the house price cycle - Ruben Tarne (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2022)
This paper investigates the dynamics of financial vulnerability of indebted homeowners over the housing cycle with an agent-based housing market model. The model is calibrated using UK micro data. I find that financial vulnerability is driven by previous period house purchases and by dissaving due to a wealth effect on consumption. While the first channel is more important in the upswing, the dissaving channel is more important at high price levels. A second finding is that current vulnerability is path-dependent on past purchases at high prices, as due to the wealth effect, these past purchases lead to temporary high consumption.
Keywords: G51; C63; R31; 330; house price cycle